Reseña de Manovich, Lev. The Science of Culture? Social Computing, Digital Humanities and Cultural Analytics, Journal of Cultural Analytics, 1(1), 1-15. 2016 - Avellaneda, Nicolás (2021)
Reseña de Manovich, Lev. The Science of Culture? Social Computing, Digital Humanities and Cultural Analytics, Journal of Cultural Analytics, 1(1), 1-15. 2016.